Fintech And Financial Innovation: Online Transportation Services In The Perspective Of Shari'ah Economic Law - Kulsum, Sayyidah Sekar Dewi; Aprilianti, Aprilianti (ASAS, 2024)
Fintech are constantly undergoing updates along with the times, one of which is the Online Transportation business, which is an internet application-based public transportation service that can be used instantly via a smartphone application. The novelty of the mechanism and the convenience offered in this service of course also give rise to various new problems that may occur in the engagement. Therefore, the following problem formulation is presented: 1. How is the online transportation service engagement at PT Ujung Drajad, and 2. What is the Sharia Economic Law analysis of this engagement. This research aims to find out as clear an answer as possible regarding the formulation of the problem under study. The research method used is field research. Data processing was carried out using qualitative methods with an inductive thinking approach. From the findings of this research, there are inconsistencies between the Agreement and its implementation. There is different treatment from the company (PT Ujung Drajat) towards Titip Bendera drivers between those with family status and those without. For those who are family, they are charged 7% of their weekly income, while for drivers who are not family, they are charged 10%. There is a reduction in car rental prices for drivers who have a lot of rental arrears, namely from 200,000 per day to 150,000 per day. Based on the analysis of Islamic law, on the one hand, the agreement has fulfilled the pillars, conditions and principles of the agreement. On the other hand, there are those who violate the principles of justice and the principles of equity and equality in the principles of Islamic relations. However, in general, this agreement is legally permissible. According to its form, this agreement is an ordinary agreement (contract) in the form of cooperation (syirkah) and lease (ijaroh).Keywords: Partnership; Online Transportation; Islamic Law;